Shanghai Cooperation Organization and Its Implications for the United States - Ihsan Ali; Jamal ud Din; Sami Ullah (ASIAN Journal of International Peace & Security (AJIPS), 2022)
The United States wanted to join the Shanghai Cooperation Organization (SCO) in order to maintain a strong influence in the region, but it was rejected. As a regional player, the organization poses a threat to US interests and dominance in the region. Since there is no direct confrontation between the US and the SCO, the two are still working against each other to denigrate each other. The objectives of the current study are to explore and investigate the US-SCO areas of convergence and divergence. Further analysis and examination of how the SCO may affect the United States is also part of the existing study. This study uses historical, descriptive, and analytical approaches. The current research is qualitative in nature, and the data has been collected from secondary sources. These sources include authentic research papers, annual reports, books, research articles, newspaper articles, and historical records that address various aspects of the study. According to the findings of this study, the organization quickly developed a "global strategic group" that has raised concerns about US influence and interests not just in Central Asia but also in the Middle East and East Asia.